2022
DOI: 10.3389/fgene.2022.917142
|View full text |Cite
|
Sign up to set email alerts
|

Causal Inference of Genetic Variants and Genes in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal progressive multisystem disorder with limited therapeutic options. Although genome-wide association studies (GWASs) have revealed multiple ALS susceptibility loci, the exact identities of causal variants, genes, cell types, tissues, and their functional roles in the development of ALS remain largely unknown. Here, we reported a comprehensive post-GWAS analysis of the recent large ALS GWAS (n = 80,610), including functional mapping and annotation (FUMA), transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
2
1
0
Order By: Relevance
“…Secondly, we meticulously selected multiple tissue datasets with the largest sample size and rigorously conducted verifications using various instrumental variable selection criteria, thereby enhancing the credibility of our findings. Furthermore, our study also validated partial findings from previous research, such as TBK1 [13], a druggable target identified in our study; however, it was not reported as a prioritized drug target for ALS in other studies [23,[88][89][90]. Additionally, we have made novel discoveries by identifying new druggable genes in blood samples, brain tissue, and spinal cord (e.g., TNFSF12, TNFSF13, and RESP18), which offer promising avenues for future investigation of ALS drugs.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, we meticulously selected multiple tissue datasets with the largest sample size and rigorously conducted verifications using various instrumental variable selection criteria, thereby enhancing the credibility of our findings. Furthermore, our study also validated partial findings from previous research, such as TBK1 [13], a druggable target identified in our study; however, it was not reported as a prioritized drug target for ALS in other studies [23,[88][89][90]. Additionally, we have made novel discoveries by identifying new druggable genes in blood samples, brain tissue, and spinal cord (e.g., TNFSF12, TNFSF13, and RESP18), which offer promising avenues for future investigation of ALS drugs.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in the rs2453555_C9orf72 locus, although the candidate consensus SNP was determined as rs143956135, a nearby SNP, rs2453555, was also reported by one method (PolyFun + SuSiE) with a high posterior probability (PP = 0.9). Furthermore, COLOC analysis revealed that rs2453555 showed significant colocalization signals with eQTL (PP4 = 0.81, PP4/PP3 = 5.8) or sQTL in brain (PP4 = 0.97, PP4/PP3 = 30.7) (Figure 3B , Supplementary Table S6 ), which was in line with our previous study ( 50 ).…”
Section: Database Content and Usagesupporting
confidence: 91%
“…By using three TWAS methods (S-PrediXcan, UTMOST and JTI), we identified a total of 102 genes significantly associated with ALS by at least two methods (FDR < 0.05), of which 19 were reported in recent GWAS and post-GWAS studies ( 46 , 50 , 51 ) ( Supplementary Table S4 ), leaving a large number of newly identified candidate genes for ALS. By using the SMR analysis, we tested the exposure measurements from six types of cis-xQTLs and identified a total of 84 genes with significant evidence that likely mediated the genetic associations (FDR < 0.05 and HEIDI > 0.05).…”
Section: Database Content and Usagementioning
confidence: 99%
“…283 The cerebellum in ALS also has exhibited oxidative stress abnormalities, 284 mitochondrial damage, 285 neurotransmitters and receptors changes, 277 and gene changes (Figure 3). 286,287 Structural and functional imaging studies have revealed structural and functional alterations in the cerebellum of ALS patients. 288 Several studies have demonstrated cerebellar atrophy in ALS, 257,289,290 affecting both cerebellar grey matter, [291][292][293][294] and cerebellar white matter.…”
Section: Cerebellum and Alsmentioning
confidence: 99%
“…The cerebellum in ALS also has exhibited oxidative stress abnormalities, 284 mitochondrial damage, 285 neurotransmitters and receptors changes, 277 and gene changes (Figure 3). 286,287 …”
Section: Cerebellum and Other Ndsmentioning
confidence: 99%